التغير العشوائي لاستعمالات الارض في الاحياء السكنية لبلدية الاعظمية (Journal of the College of Basic Education, 2026)
The change in the area of ​​land use in reviving the study area has been revealed based on the visual interpretation of high-resolution spatial (60 cm / 1 m) satellite and space-wide (30 m) spacecraft (world-wide) 30 moon space imagery. And the basic design map prepared by the Paul Service Foundation for the year 1973, as well as aerial photographs taken of the study area during the nineties and seventies, through which it was possible to measure the spatial change for the period 1973-2024. In addition to applying certain algorithms in the ERCDAS8.5 program such as the NDVI vegetative guide interested in diagnosing agricultural and open areas where the current study was based on RS remote sensing techniques and GIS as an applied basis in extracting spatial changes to land uses. And to detect spatial and temporal variations That contributed to changing the uses of the land in the study area for the period (1973-2024) and that resulted in a change in the class of use in the study area, which indicates the spatial acquisition of residential use on the area of ​​the rest of the other uses (agricultural, commercial, industrial, service).